Effect of Current Ratio, Return on Assets, and Firm Size on Debt Policy Indonesia 2022–2025 - Adhe Marselina Putri; Purwo Atmojo; Dika Karlinda Sari (Cita konsultindo, 2026)
This study examines the effects of Current Ratio (CR), Return on Assets (ROA), and Firm Size on debt policy in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2025 period. The study is motivated by the capital-intensive nature of the mining industry, which requires substantial external financing and makes debt policy a crucial financial decision. Previous empirical studies have reported inconsistent findings regarding the influence of liquidity, profitability, and firm size on debt policy, indicating the existence of a research gap. This study employs a quantitative research design using secondary data obtained from the annual financial statements of mining companies listed on the IDX. The sample consists of 86 firm-year observations selected through purposive sampling. The hypotheses are tested using multiple linear regression analysis with IBM SPSS version 27. The empirical findings reveal that Current Ratio has a positive and significant effect on debt policy, whereas Return on Assets and Firm Size do not significantly influence debt policy. These findings provide updated empirical evidence regarding the determinants of debt policy in Indonesian mining companies and contribute to the development of Agency Theory in explaining corporate financing decisions within capital-intensive industries.